Preservation characteristics of UASB sludges - (:unkn) unknown (MARCEL DEKKER INC, 1997)
Anaerobic treatment has become popular as an effective means for the treatment of high strength wastewaters, however, quantitative research on the preservation characteristics of anaerobic sludges is necessary when an anaerobic reactor is considered for use in industries operating intermittently. This research investigated preservation characteristics of anaerobic sludges in terms of storing age and environmental conditions. For this purpose, sludge obtained from a full scale reactor was used as seed sludge for several laboratory scale batch reactors. After cultivation, the reactors were stored at room temperature, 4 degrees C, -18 degrees C, and 37 degrees C without feeding for different storage periods up to 12 months. After storage, changes in physicochemical and microbial characteristics were monitored in terms of storing period and temperature. VSS, TSS, COD ir the liquid phase were measured. Microbial activities were expressed as specific methanogenic activity. The results indicated that anaerobic sludges can be effectively used for intermittently produced wastewaters.
Keywords: anaerobic; storing; preservation; temperature; bioactivity; METHANOGENIC ACTIVITY